METHODOLOGY FOR CONDUCTING SYNTACTIC WORK IN THE SPEECH CULTURE SYSTEM OF PRIMARY SCHOOL STUDENTS (Intent Research Scientific Journal, 2024)
In this article, how to carry out syntactic works in the system of developing the speech of students in native language classes, syntactic works in the process of teaching the science of the mother tongue during the teaching process, syntactic works in writing statements and essays, speech connection, word combinations and sentences trained to work.